HBV reactivation in rheumatic diseases patients under therapy: A meta-analysis. (January 2018) - Moghoofei, Mohsen; Mostafaei, Shayan; Ashraf-Ganjouei, Amir; Kavosi, Hoda; Mahmoudi, Mahdi
Abstract: Background: Hepatitis B is one of the most common infectious diseases worldwide. In patients undergoing immunosuppressive therapy such as rheumatic diseases, reactivation of hepatitis B virus (HBV) is considered clinically important. This systematic review and meta-analysis were performed to determine the prevalence rate of HBV reactivation in rheumatic patients from different parts of the world. Methods: The authors performed a systematic literature review from several reliable databases including Scopus, ISI Web of Science and PubMed. Furthermore, the keywords of this research were "Hepatitis B virus", "Rheumatic diseases", "HBV reactivation", "Anti-TNF", "DMARDs" and "Biologic agents". Results: The authors selected 30 studies out of 983 for the present review. The overall estimation of the prevalence of HBV reactivation was 1.4 (95% confidence interval (CI): 1.3–1.6). Also, the heterogeneity in estimating the pooled prevalence among the studies was shown; Cochran Q test, P  < 0.001, I 2  = 99.9%. It should be noted that max and min reactivation rate of HBV were in Italy and France respectively. Conclusions: Rheumatic disease patients with resolved hepatitis B should be tightly monitored for possible HBV reactivation by elevation of liver enzymes and HBV DNA levels. Highlights: Hepatitis B is one of the most common infectious diseases worldwide. In patients with rheumatic diseases undergoing immunosuppressive therapy, reactivation of HBV is considered clinically important. Rheumatic patients with resolved hepatitis B should be monitored for possible HBV reactivation by measuring liver enzymes and HBV DNA levels.